KLASTERISASI MENGGUNAKAN ALGORITMA K-MEANS CLUSTERING DENGAN MENGGUNAKAN INDIKATOR TOTAL DEBT TO TOTAL EQUITY RATIO, CURRENT RATIO DAN RETURN ON ASSETS UNTUK MENGETAHUI DAMPAK COVID-19 PADA 10 INDUSTRI DI BURSA EFEK INDONESIA - Kevry Ramdany; Jerry Heikal (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Clustering data is a data grouping method. This is a part of Data Mining, which is pattern extraction that interested of the big data. Clustering usually use in business intelligence, image pattern recognition, web search, field of biological sciences, and for security. Clustering is a process grouping data into clusters so that data in one cluster have the same maximum. Object in one cluster have the same characteristic between each others and different with other cluster. This research using K-means Clustering to grouping company in some industries based on available data in yahoo finance. Grouping aim to know about which good company to invest in during this pandemic. Data source financial statement in 2020 that available in yahoo finance. Analysis method using K-means clustering with software SPSS version 20. The result is 3 clusters, which is cluster 1 severely affected by covid, cluster 2 mildly affected by covid and cluster 3 moderately affected by covid. Result of analysis there is 7 companies in cluster 1, 1 companies in cluster 2, and 2 companies in cluster 3. Based on analysis result using K-means Clustering then suggested to invest on company that include in cluster 2 is Unilever Indonesia Tbk.